Odvození a vyuzití nového fyziologického kritéria pro hodnocení výkonnostní kapacity koní - Kovár, J (Veterinarni medicina, 1982)
The possibility of using the test for pulse-rate response to gradated load in the evaluation of the endurance component of horse performance (in other words, response to the degree of horse adaptation to load) is discussed in detail. A mathematic-statistical analysis of regression coefficients is performed in the equations of the dependence of pulse rate on speed obtained in 278 three years old horses in the period following the termination of the basic training (145 Bohemian Warm-Blooded horses, 115 Kladrub Black horses and 18 English Half-Breds). A ten-score scale is calculated on the basis of the quantiles of normal distribution. The performance of a tested horse can be evaluated on the basis of this scale with an actually measured regression coefficient.
Keywords: Horses; Pulse; fyzická vytrvalost; Physical Endurance; tělesná námaha; zvířata; Animals; koně; Physical Exertion; pulz